Technological Advancement In The Society 5.0 Era For Notary In Indonesia: Glory Or Obsolete? - Agustini; Nurlaily; Triana Dewi Seroja (IHSA Institute, 2022)
The development of the legal profession is changing at an extraordinary speed, such as in the field of technology. The legal needs in society will be met by new entities, including technology companies that provide document creation systems and artificial intelligence systems to support legal services. But in the era of society 5.0, with digital advances and the emergence of artificial intelligence machines and big data, this eventually led to a change in the perspective and way of individuals in terms of law, which turned into an